The Effectiveness of E-leaflets and Video on Adolescent Girls' Knowledge About Sexual Harassment Victims Protection - Shibarani Gita Pratiwi; Indriati Dwi Rahayu; Rahma Dian Hanifarizani (Oksitosin : Jurnal Ilmiah Kebidanan, 2026)
Sexual harassment is defined as any physical, verbal, or non-verbal treatment that is sexual in nature and causes the victim to experience sexual harassment.. The action is in the form of sexist jokes to rape. Midwives also need to be able to handle the problem of sexual harassment including promotive efforts to increase public knowledge regarding sexual harassment. Efforts to increase knowledge include health education. This research was held to assess the difference in effectiveness in health education with e-leaflet and video media on increasing the knowledge of adolescent girls about access to protection for victims of sexual harassment. This research was using a quasi-experimental design with the untreated control group design with dependent pre-test and post-test samples. The study was conducted in November - December 2024 to grade IX students of SMPN 2 Panji. To determine the sample, this research was using the total sampling method to obtain 58 subjects. The sample was divided randomly into 3 groups named the e-leaflet, video, and control groups. The data were tested with Kruskal-Wallis test method and obtained p 0.013 < 0.05. This value shows a significant difference between the knowledge levels of students in the e-leaflet group, video group, and control group.